Note on warped compactification. Finite brane potentials and non-Hermiticity - Sudhakantha Girmohanta; Yuichiro Nakai; Motoo Suzuki; Yaoduo Wang; Junxuan Xu (Journal of High Energy Physics)
Abstract We study radius stabilization in the Randall-Sundrum model without assuming any unnaturally large stabilizing scalar potential parameter at the boundary branes (γ) by the frequently used superpotential method. Employing a perturbative expansion in 1/γ 2 and the backreaction parameter, we obtain approximate analytical expressions for the radion mass and wavefunction. We validate them through a dedicated numerical analysis, which solves the linearized coupled scalar and metric field equations exactly. It is observed that the radion mass decreases with decreasing γ. Below a critical value of γ, the radion becomes tachyonic, suggesting destabilization of the extra dimension. We also address the issue of non-Hermiticity of the differential operator that determines the radion and Kaluza-Klein (KK) mode wavefunctions in the finite γ limit. It is accomplished by finding an explicit form of the general scalar product that re-establishes the orthogonality in the KK decomposition.